TANGGUNGJAWAB NEGARA PELUNCUR BENDA ANGKASA TERKAIT MASALAH SAMPAH LUAR ANGKASA (SPACE DEBRIS) BERDASARKAN LIABILITY CONVENTION 1972 - SILWANUS ULI SIMAMORA; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Aerospace is an air space where no gases are air or atmosphere in which there are space objects such as the moon and other celestial objects. But in the utilization of space still has not been done in a peaceful and balanced in their utilization, because the activity did not see the impact of space activities such as the creation of space debris. Space debris is a man-made celestial body that no longer work in the area of outer space. The purpose of this thesis are: First, to determine the setting launch of space objects; Second, to determine the accountability of the launching State on space debris, a former celestial body that is launched.This type of research used in this study, using normative legal research. In this research, the authors conducted a study of the principles of law which starts on applicable international agreements by identifying the rules that have been formulated in international agreements.From the research, there are three main things that can be inferred. First, the development of the launch of space objects until now largely done by space power and space activities require a very large cost. Second, Accountability launching State on space debris, a former space objects were launched into space consist of two (2) the principle of state responsibility is absolute liability, provided for in Article 2 and Article 4 (a) Liability Convention 1972 and based on fault liability , provided for in Article 3 and Article 4 (b) Liability Convention1972.Keywords: Space Debris – Responsibility - Liability Convention 1972